58. TREATMENT ADHERENCE FOR OUTPATIENTS WITH HYPERTENSION AT NGUYEN DINH CHIEU HOSPITAL, BEN TRE PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of treatment adherence among outpatients with hypertension at Nguyen Dinh Chieu Hospital, Ben Tre Province.Materials and methods: Patients diagnosed with hypertension, aged 18 and above, who are monitoring and receiving treatment at Nguyen Dinh Chieu Hospital, Ben Tre Province, and have been taking antihypertensive medication for at least 3 months.Results: The survey on 300 patients showed the following results: Knowledge adherence rate ( 65.5%); attitude adherence rate ( 89.5%); medication adherence rate ( 89.8%); overall treatment adherence rate ( 69,6%). Some areas that need improvement include basic knowledge about hypertension (normal blood pressure levels, risk factors, causes, and consequences), daily blood pressure monitoring, and forgetfulness in taking medications.Conclusion: There is a need for appropriate solutions to improve treatment adherence for outpatients with hypertension at Nguyen Dinh Chieu Hospital, Ben Tre Province, from 2025 to 2026.
Keywords: Hypertension, treatment adherence, health education, disease management, Nguyen Dinh Chieu Hospital.